(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
This paper attempt to examine constraints to teaching and learning physical education and sports in Nigeria. It examine the concept of physical education and school sports, principles of physical education and school sports programmes, types of school sports activities, objectives of physical education and school sports in Nigeria. Also, physical education and school sports at different educational levels i.e. at both primary, secondary schools as well as at tertiary level. Facilities and equipment were discussed, conclusion and recommendations were also offered as follows: School Sports training and organization and physical activities should be made mandatory in primary, junior and senior secondary schools in Nigeria, the curriculum for primary, junior and senior secondary schools sports programmes and organization and physical activities should not just include school sports motivation but also competitive sports.